The cat who came to breakfast - Braun, Lilian Jackson (New York : Jove Books, 1995)
When a cabin cruiser mysteriously explodes in the marina of Breakfast Island, newspaper reporter Jim Qwilleran and his feline companions investigate shady happenings at the hot vacation spot.
Originally published: New York : Putnam, c1994., D., 4/2006, R Troeger in memory of Lorraine Troeger
Keywords: Qwilleran, Jim (Fictitious character) -- Fiction; Journalists -- United States -- Fiction; Cats -- Fiction; Mystery fiction